2023
DOI: 10.1002/srin.202300119
|View full text |Cite
|
Sign up to set email alerts
|

Formation Mechanism and Control Technology of Transverse Corner Cracks During Slab Continuous Casting of Microalloyed Steels

Miaoyong Zhu,
Zhaozhen Cai

Abstract: Microalloyed steel with Nb, V, Ti, and other alloying elements is one of the important steel grades in the steel industry. During continuous casting process, high occurrence rate of transverse corner cracks in slabs restricts the quality and efficiency of the production of microalloyed steel grades, and it has not been effectively solved for a long time. Herein, the research progress on the formation mechanism, influential factors, and typical control technologies of transverse corner cracks during slab contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 80 publications
(128 reference statements)
0
1
0
Order By: Relevance
“…The formation of cracks is closely related to the evolution of the microstructure stage and mechanical properties of the slab during the high-temperature continuous casting process [6][7][8]. Brimacombe et al [9] and Suzuki et al [10,11] indicated the presence of three typical brittle zones in the hot ductility evolution during the continuous casting process.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of cracks is closely related to the evolution of the microstructure stage and mechanical properties of the slab during the high-temperature continuous casting process [6][7][8]. Brimacombe et al [9] and Suzuki et al [10,11] indicated the presence of three typical brittle zones in the hot ductility evolution during the continuous casting process.…”
Section: Introductionmentioning
confidence: 99%